Portugal : Financial Sector Assessment Program; Detailed Assessment of Observance of IOSCO Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2007)
This Detailed Assessment of the Observance of International Organization of Securities Commissions (IOSCO) Objectives and Principles of Securities Regulation for Portugal assesses the securities market. The legal and regulatory framework authorizes banks to provide investment services under a universal banking model. Two main cash markets operate in Portugal: Eurolist, operated by Euronext Lisbon, and the Mercado Especial de Divida Publica (MEDIP), operated by MTS Portugal S.A. The authorities broadly concur with the assessment, and welcome the overall judgment that the Portuguese framework is highly compliant with IOSCO Principles.